Temperament Distinguishes Persistent/Recurrent from Remitting Anxiety Disorders Across Early Childhood. Issue 6 (2nd November 2018) - Bufferd, Sara J.; Dougherty, Lea R.; Olino, Thomas M.; Dyson, Margaret W.; Carlson, Gabrielle A.; Klein, Daniel N.
Abstract : Up to 20% of preschool-age children meet criteria for anxiety disorders and, for a large subset, anxiety appears to persist throughout early childhood. However, little is known about which factors predict persistence/recurrence of anxiety in young children. Temperament, including behavioral inhibition (BI), negative emotionality (NE), and positive emotionality (PE), predict the onset of anxiety disorders, but to our knowledge no study has examined whether temperament predicts the course of anxiety in young children. From a community sample of 3-year-olds, we identified 89 children (79.8% White, non-Hispanic; 41.6% female) who met criteria for an anxiety disorder and examined whether observed and parent-reported BI, NE, and PE at age 3 distinguished children who continued to meet criteria for an anxiety disorder from those who remitted by age 6. Higher levels of BI and lower levels of PE assessed in the laboratory and higher parent-reported BI and shyness and lower surgency at age 3 significantly predicted persistence/recurrence of anxiety disorders from age 3 to 6. These data are the first to demonstrate the influence of temperament on the course of anxiety disorders in young children. These findings can enhance assessment and treatment of anxiety by focusing intervention efforts on children who are at risk for persistent or recurring anxiety rather than children who are displaying transient, and possibly developmentally normative, anxiety.